Association of physical activity, screen time and sleep with substance use in children and adolescents: a large sample cross-sectional study - Su, Huadong; Lyu, Dongye; Huang, Ke; Yan, Jin (Frontiers in Public Health, 2024)
Background: 24-hour movement guidelines (24-HMG) play an important role in various demographics such as early years, children, youth, and the elderly. Nevertheless, most existing research exploring the links between socioeconomic factors, dietary intake, and substance use with sleep patterns, physical activity (PA), and sedentary behaviour (SB) has been conducted in high-income Western countries. Purpose: Hence, this study seeks to investigate the relationship between adherence to the 24-HMG and smoking and alcohol use behaviours among children and adolescents in China. Methods: A comprehensive survey, in collaboration with the Municipal Education Commission, was carried out across primary and middle schools in Shenzhen, China. Sleep duration was gauged using the Pittsburgh Sleep Quality Index (PSQI), screen time was assessed with items adapted from the Health Behavior of School-aged Children (HBSC) survey, and PA was measured using a single item adapted from the HBSC survey. Results were presented as odds ratios (ORs) with 95% confidence intervals (CIs), considering p-values below 0.05 as statistically significant. Results: Among the sample, 51.9% were boys and 48% were girls. Those who did not meet any guidelines had a higher probability of smoking (OR = 1.62 [95% CI: 1.03, 2.56], p = 0.037) among children and adolescents. Conversely, meeting one (OR = 0.94 [95% CI: 0.61, 1.52], p = 0.874) or two guidelines (OR = 0.84 [95% CI: 0.52, 1.34], p = 0.459) showed no significant impact. The data displayed an inverse correlation between the number of guidelines adhered to and the likelihood of alcohol use among children and adolescents: none (OR = 2.07, p < 0.001), one guideline (OR = 1.40, p = 0.006), and two guidelines (OR = 1.22, p = 0.106).Not meeting guidelines elevates smoking and alcohol use risks in children and adolescents, whereas following more guidelines lowers these risks, highlighting the importance of guideline adherence in reducing substance use.